Recognition of speech presented at soft to loud levels by adult cochlear implant recipients of three cochlear implant systems. - Firszt JB; Holden LK; Skinner MW; Tobey EA; Peterson A; Gaggl W; Runge-Samuelson CL; Wackym PA; Firszt, Jill B; Holden, Laura K; Skinner, Margaret W; Tobey, Emily A; et al. (Ear & Hearing (01960202), 2004)
Objective: The purpose of this study was to conduct a large-scale investigation with adult recipients of the Clarion, Med-El, and Nucleus cochlear implant systems to (1) determine average scores and ranges of performance for word and sentence stimuli presented at three intensity levels (70, 60, and 50 dB SPL); (2) provide information on the variability of scores for each subject by obtaining test-retest measures for all test conditions; and (3) further evaluate the potential use of lower speech presentation levels (i.e., 60 and/or 50 dB SPL) in cochlear implant candidacy assessment.Design: Seventy-eight adult cochlear implant recipients, 26 with each of the three cochlear implant systems, participated in the study. To ensure that the data collected reflect the range of performance of adult recipients using recent technology for the three implant systems (Clarion HiFocus I or II, Med-El Combi 40+, Nucleus 24M or 24R), a composite range and distribution of consonant-nucleus-consonant (CNC) monosyllabic word scores was determined. Subjects using each device were selected to closely represent this range and distribution of CNC performance. During test sessions, subjects were administered the Hearing in Noise Test (HINT) sentence test and the CNC word test at three presentation levels (70, 60, and 50 dB SPL). HINT sentences also were administered at 60 dB SPL with a signal-to-noise ratio (SNR) of +8 dB. Warble tones were used to determine sound-field threshold levels from 250 to 4000 Hz. Test-retest measures were obtained for each of the speech recognition tests as well as for warble-tone sound-field thresholds.Results: Cochlear implant recipients using the Clarion, Med-El, or Nucleus devices performed on average equally as well at 60 compared with 70 dB SPL when listening for words and sentences. Additionally, subjects had substantial open-set speech perception performance at the softer level of 50 dB SPL for the same stimuli; however, subjects' ability to understand speech was poorer when listening in noise to signals of greater intensity (60 dB SPL + 8 SNR) than when listening to signals presented at a soft presentation level (50 dB SPL) in quiet. A significant correlation was found between sound-field thresholds and speech recognition scores for presentation levels below 70 dB SPL. The results demonstrated a high test-retest reliability with cochlear implant users for these presentation levels and stimuli. Average sound-field thresholds were between 24 and 29 dB HL for frequencies of 250 to 4000 Hz, and results across sessions were essentially the same.Conclusions: Speech perception measures used with cochlear implant candidates and recipients should reflect the listening challenges that individuals encounter in natural communication situations. These data provide the basis for recommending new candidacy criteria based on speech recognition tests presented at 60 and/or 50 dB SPL, intensity levels that reflect real-life listening, rather than 70 dB SPL.